An ultra-wide rejection suppressing cell for microwave applications - Farzin Shama; Milad Ekhteraei; Mohsen Hayati; Hamed Abbasi (PLoS ONE, 2026)
This paper presents the design and fabrication of a novel suppressing cell (SC) implemented on a RO4003 substrate for microwave circuit applications. Experimental results indicate that the SC functions as a low-pass filter (LPF) with a 3 dB cutoff frequency at 5.7 GHz and a transition band of 0.6 GHz from −3 dB to −20 dB. The design achieves an ultra-wide stopband from 6.3 GHz to 50 GHz, with significant attenuation noted in the S22 parameter around 38 GHz, effectively covering five harmonics of the cutoff frequency. The return loss in the passband is measured at 10 dB, with an insertion loss of just 0.5 dB at 1.3 GHz. Additionally, the size of the SC is compact at 15.3 mm × 10.5 mm (15.3 λg × 10.5 λg), and the group delay in the passband exhibits minimal variation, recorded at only 0.53 ns.